Effect of feed temperature on concentration polarization and efficiency of reverse osmosis systems - Khalaf, Taha Yaseen (Nahrain University College of Engineering Journal, 2008)
The objective of the present study was to investigate the effect of temperature in order to improve the efficiency of the RO desalination process, and analyze the concentration polarization in spiral wound salinity water membrane elements. In this study the commercial reverse osmosis membrane (cellulose acetate) have been used to treat medium concentrated (NaCl) salt solutions up to 1200 ppm. The results of the experiments show that the polymer membrane is very sensitive to changes in the feed temperature, and the concentration polarization variation with increase in flow rate and with decrease in temperature. The nonlinear equation obtained is solved numerically using the Marquardt method to determine various parameters. The k values estimated from the model show a marked variation that may be attributed to the presence of reflection coefficient in the Spiegler-Kedem model. It is suggested that the combined Spiegler- Kedem/film theory model may be the best method for establishing the mass transfer correlation for a given membrane of reverse osmosis and nanofiltration.